The minimal effective dose of Nordic hamstring exercise for reducing hamstring strain injuries in football (soccer) - Gentilcore, D. R. (Journal of Australian Strength and Conditioning, 2018)
The use of Nordic hamstring exercise (NHE) programs can significantly reduce the incidence of hamstring strain injuries (HSI) in football, however a better understanding of the minimal effective dose required may improve confidence in the prescription, and compliance amongst athletes. ABSTRACT The aim of this paper is to review the literature on different NHE programs found to reduce the incidence of HSI in football (soccer) and compare dose/volumes in order to determine what may be a minimal effective dose of NHE. An electronic literature search was completed up to June 2017 via Research Gate, PEDro and Google Scholar databases. Five studies met the inclusion criteria, with all studies outlining different NHE doses (average reps/session = 24-34; average reps/week range = 57-72). Two studies reported a 65-70% decrease in HSI incidence, whilst the other three reported significant improvements in physiological factors identified as key risk factors for HSI (fascicle length +1.58-1.8cm, eccentric hamstring torque +11-31%, and peak hamstring strength +7-12%). There is convincing evidence suggesting a NHE program can significantly reduce the incidence of HSI in football, therefore S&C coaches/physiotherapists working in football should strongly consider the implementation of NHE within weekly programs. However, the minimal effective dose required in order to achieve injury preventative physiological changes whilst exposing the athlete to as little additional hamstring stress/fatigue as possible remains unclear. It is recommended that NHE programs are progressed in volume gradually due to the demanding/fatiguing nature the exercise. Volumes as low as 2 sets of 3 reps once per week, or as high as 3 sets of 10 repetitions twice per week, with linear progression as gradual as 4 additional repetitions per week, may be advised. It is encouraged that these sessions are performed after football training, on days that precede a day off from training, in order to allow for adequate recovery before the next training session.